DISTRO SEBAGAI PROVIDER GAYA HIDUP “ALTERNATIF”: MENENGOK STRATEGI DISTRO DALAM USAHANYA MEMPERTAHANKAN EKSISTENSI - Zakiyah Derajat (Jurnal Kawistara, 2013)
Distro (distribution outlet/distribution store), with its DIY (Do-It-Yourself) and independent ethos, hasever been so popular in Yogyakarta as youth’s field to express their self. Decade passed, youth changed,distro still exists, but now it is merely the “alternative” of the big (ie. mall). Descriptive qualitative researchbased on field ethnography within May and June 2013, I would discuss the strategy of Demangan distroarea (Jl. Cendrawasih, Yogyakarta), in forming their nowadays identity in order to remain exist. Thediscussion shows that there are some of their stratregies: by converging in one area and structuringdistro region, by interior design, and by not-that-indie (at all) identity. The lower number of distro andits attempt of forming its DIY-ethos-ed youth indicate that the youth are now, to a certain extent, notinterested in producing and distributing. Hence, most of them are no more than the object of capitalism,which is by consuming.